The Effectiveness of Emotional Intelligence Training on Marital Burnout and the Quality of Marital Relationships in Couples Aged 20 to 50 - Sayadi Kenari , Seyedeh Somayeh; Gholipor , Forozan; Mazlomi, Maryam; Katal, Hengame (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to examine the effectiveness of emotional intelligence training on reducing marital burnout and improving marital relationship quality among couples aged 20 to 50 who referred to counseling centers. Methods and Materials: The study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of couples aged 20 to 50 who referred to counseling centers in Babol County in 2024. Using convenience sampling, 32 couples were selected and randomly assigned to an experimental group and a control group, each comprising 16 participants. Data were collected using the Pines Marital Burnout Questionnaire and the Marital Relationship Quality Questionnaire. The experimental group received emotional intelligence training in 12 structured sessions of 90 minutes, conducted twice weekly, while the control group received no intervention. Pretest and posttest assessments were administered to both groups, and data were analyzed using descriptive statistics and univariate analysis of covariance (ANCOVA) in SPSS version 27. Findings: After controlling for pretest scores, ANCOVA results revealed a statistically significant group effect for marital burnout, indicating that the experimental group reported significantly lower posttest burnout scores compared to the control group. Similarly, a significant group effect was found for marital relationship quality, demonstrating that participants who received emotional intelligence training showed significantly higher posttest marital quality scores than those in the control group. Effect size indices indicated large and meaningful intervention effects for both outcome variables. Conclusion: The findings indicate that emotional intelligence training is an effective intervention for reducing marital burnout and enhancing marital relationship quality among couples seeking counseling services, highlighting the importance of emotional competence development in marital counseling and preventive family interventions.